Fast electron beam measurements from relativistically intense, frequency-doubled laser-solid interactions - Scott, R; Pérez, F; Streeter, M; Clark, E; Davies, JR; Schlenvoigt, H; Santos, J; Hulin, S; Lancaster, K; Dorchies, F; Fourment, C; Vauzour, B; et al. (2013)
Experimental measurements of the fast electron beam created by the interaction of relativistically intense, frequency-doubled laser light with planar solid targets and its subsequent transport within the target are presented and compared with those of a similar experiment using the laser fundamental frequency. Using frequency-doubled laser light, the fast electron source size is significantly reduced, while evidence suggests the divergence angle may be reduced. Pyrometric measurements of the target rear surface temperature and the Cu Kα imager data indicate the laser to fast electron absorption fraction is reduced using frequency doubled laser light. Bremsstrahlung measurements indicate the fast electron temperature is 125 keV, while the laser energy absorbed into forward-going fast electrons was found to be 16 ± 4% for frequency doubled light at a mean laser intensity of 5 ± 3 × 1018 W cm-2. © IOP Publishing and Deutsche Physikalische Gesellschaft.